Grappling with the learning modules: Experience of Public Elementary Pupils Attending English Written Modular Classes - Panganiban, Gladys L.; Madrigal, Dennis V. (Technium Social Sciences Journal, 2021)
Modular Distance Learning is one of the educational trends brought about by the pandemic. The recent use of this model of learning delivery has put teaching and learning into an adjustment period. This particular challenge has been the urgent imperative to have modular classes. It implies designing and organizing for better learning. English is the primary medium of instruction in education, and most of the modules written in the given language posing additional challenges and demands to school learners. Hence, this paper endeavors to investigate the lived experiences of the pupils in answering English-written modules through a qualitative design with a phenomenological approach. The participants of the study were eight Grade 6 pupils determined using the purposive sampling technique with some inclusion criteria. Data were gathered through an in-depth interview and were analyzed using a recursive textual analysis aided by Lichtman’s 3c's: coding, categorizing, and conceptualizing. The study revealed that quality education in the locality during this time of pandemic is greatly affected by the delivery modality, the curriculum content and standards, educational equipment and resources, the competence of parents to give assistance, and the readiness of the learners to read and learn independently.